Knowledge and utilization of stillbirth preventive measures among women in childbearing age (mbala district) - SR Chansa, Regina (Lusaka: University of Zambia, School of Medicine, 2012)
The main aim of the study waa to establish knowledge and utilization of stillbirth preventive measures which are knowledge service related, health behavioral factors, disease related, health behavioral factors, disease related and social-cultural-economic factors.
Includes bibliographical references .
Keywords: stillbirth --mbala district; stillbirth --mbala district --prevention.; stillbirth --etiology --mbala district